Let the King Rest in Peace: Human Impact (Teasing Behaviour) at Asiatic Lion Exhibit in Mysore Zoo - Raju, R.; Venugopal, B. (Indian Forester, 1994)
Teasing behaviour was observed at the Asiatic Lion exhibit in the Mysore Zoo. An averages of 11% of visitors were teasers. A majority of teasers were males. The hypothesis that the frequency of teasing is inversely proportional to the age-group of the visitor, was only partially proved; and more data are needed to verify it. Eventhough children may be the primary motivators for Zoo visits, they may not be Culprits for teasing.